Evaluation of anticancer activity in vitro and in vivo of iridium(iii) polypyridyl complexes. (17th May 2019) - He, Miao; Yi, Qiao-Yan; Zhang, Wen-Yao; Bai, Lan; Du, Fan; Gu, Yi-Ying; Liu, Yun-Jun; Wei, Peng
Abstract : Three new iridium(iii ) polypyridyl complexes were synthesized. The cytotoxic activity in vitro and in vivo, apoptosis, cell cycle arrest, mitochondrial membrane potential, ROS and the expression of Bcl-2 family proteins were investigated. Abstract : In this study, we designed and synthesized three new iridium(iii ) complexes [Ir(ppy)2 (dmdppz)](PF6 ) (ppy = 2-phenylpyridine) (1 ), [Ir(bzq)2 (dmdppz)](PF6 ) (bzq = benzo[ h ]quinolone) (2 ) and [Ir(piq)2 (dmdppz)](PF6 ) (piq = 1-phenylisoquinoline, dmdppz = 5, 8-dimethoxylpyrido[3, 2- a :2′, 3′- c ]phenazine) (3 ). All the complexes were tested for anticancer activity by the 3-(4, 5-dimethylthiazole)-2, 5-diphenyltetrazolium bromide (MTT) method. These complexes showed high anticancer activity against SGC-7901 cells, and the IC50 values are 4.1 ± 0.5 for1, 0.7 ± 0.1 for2 and 0.6 ± 0.2 μM for3 . Additionally, complex3 can inhibit the tumor growth in xenograft nude mice in vivo with an inhibitory percentage of tumor growth of 48.21%. Morphological studies show that the cells treated with the complexes exhibit typical apoptotic morphological characteristics such as nuclear fragmentation and chromatin condensation. Quantitative analysis by flow cytometry showed that the apoptosis rate increased sharply after the cells were exposed to the complexes, and NAC (an inhibitor that inhibits the production of ROS) can inhibit the increase of the apoptosis rate. Cell cycle studies show that complex1 can block the SGC-7901 cell cycle at the G0/G1 phase, and complexes2 and3 can cause cycle arrest at the S phase. All the complexes can increase the intracellular reactive oxygen species level, and reduce the mitochondrial membrane potential, which further prompts the release of cytochrome c . In addition, the complexes can damage DNA and cause disruption of the microtubule network. In conclusion, the complexes can effectively induce cancer cell apoptosis and may be potential anticancer agents for gastric cancer.